The regional environment dominates in shapinghuman gut microbiota - Chen Juanjuan; Wang Qi; Sun Hui (生物医学转化, 2020)
The gut is the largest microbial habitat in the human body. Gut microbial structural and functional changes were related to the occurrence and development of a variety of diseases in human, particularly the metabolic and autoimmune diseases. Multiple factors including host age, regional environment, region, dietary habits and lifestyle, diseases, drugs, hormone levels can all affect the gut microbial homeostasis. Dietary habits and lifestyle not only shape the gut microbiota in the short term, but also the most effective methods to regulate gut microbes for long. Gut microbial differences were reported to derive from the host genetics, but a recent study have showed the individuals living in the same environment, sharing similar dietary habits and lifestyles have more similar gut microbial composition and function rather than host genetics since it only explain 1.9% differences between individuals[1]. He et al also reported that the regional variation is the main factor to affect the gut microbiome in a Chinese cohort[2]. These results on the one hand suggest that the regional environment, dietary habits and lifestyle should be fully considered in the gut microbial studies, especially in those clinical intervention study, onthe other hand, it also reminds us of the importance and value of studying regional specific gut microbiota. China is a vast country, rich in regions and numerous nationalities. However, the gut microbial research in China hitherto is mostly concentrated in the southeast coastal cities, which is quite scarce in northwest China. The northwest China located in the plateau region with high altitude, low oxygen pressure and large variations in the temperature between day and night, which have created a relatively unique living environment, dietary habits and lifestyles. Plentiful of ethnic minorities have lived in the northwest China, such as Tibetans, Hui, Dongxiang, Yugu, etc. Therefore, it is of great value to study the gut microbiota of the minority populations in northwest China, not only to explore the relationship between health and diseases in the population under specific regional environment, dietary habits and lifestyles, but also helps to find novel strains to decrease the incidence of highly lethal local diseases and miscellaneous diseases in other regions based on the gut microbiota[2].